Ethnopharmacological Properties of African Medicinal Plants for the Treatment of Neglected Tropical Diseases - Gareeballah Osman Adam*; Shang-Jin Kim; Chukwuebuka Egbuna; Hong-Geun Oh (Iranian Society of Pharmacognosy, 2022)
Agriculture is considered the primary source of income and livelihood in Africa. It is rational for people to look around their environment for food and medicine. The African legacy regarding the traditional use of medicinal plants is vast and diverse, due to cultural myths and economic logic. This review briefly defines the neglected tropical diseases and surveys African medicinal plants used for neglected tropical diseases. In Africa, people may share several plants for similar diseases, e.g., Nicotiana tabacum L. and Ricinus comminus L. are used for treating Buruli ulcer infection. Folkloric African plants for the treatment of bacterial, fungal, and viral neglected tropical diseases are listed and reported in the first parts. Medicinal plants for curing parasitic neglected tropical diseases are tabulated. A plethora of medicinal plants and bioactive compounds and their preparation methods, such as macerations and boiling are reported. This report reflects the richness of Africa with medicinal plants and herbal preparations being used for the treatment of various diseases, including neglected tropical diseases. Scientific investigation of these plants has yet to be conducted to isolate the active components and determine any toxic activities. Besides, knowledge of the mechanism of action behind these beneficial effects is highly required. This review will draw the attention of pharmaceutical companies and research institutions to examine the plants presented here for further laboratory analysis and experiments.